Canine Caregivers: Paradoxical Challenges and Rewards - Lori R. Kogan; Jean E. Wallace; Peter W. Hellyer; Eloise C. J. Carr (Animals, 2022)
Companion dogs are increasingly popular, 38.4% of households in the United States include at least one dog. There are numerous benefits to sharing one’s home with a dog, but because they age more rapidly than people and have shorter lifespans, acquiring a dog often includes caring for it during its senior years. Caring for an elderly dog can be physically and emotionally challenging, yet the impact on guardians’ lives when caring for an aging dog has received minimal scientific attention. This study was designed to better understand dog guardians’ experiences and perceptions related to caring for their aging dog. Utilizing an exploratory mixed methods design, this study asked dog guardians to complete an online anonymous survey. From a total of 284 participants, we found that the impact on guardians when caring for an aging dog appears to share many similarities with caregivers of human family members. Our quantitative and qualitative results suggest that, for many guardians, caring for an aging dog is a complex dynamic with both positive and negative factors that offers an opportunity to deepen the human-animal bond and create positive, rewarding experiences and memories.